A thicker intima‐media carotid wall was found in a cohort of children with recent onset migraine. (December 2016) - Parmeggiani, Lucio; Salandin, Michela; Egger, Flavio; Lupi, Fiorenzo; Primerano, Marco; Radetti, Giorgio
Abstract: Aim: Migraine affects approximately 10–20% of the general population, including children and adolescents, and an association between migraine and increased risks for cardiovascular disease and stroke have been reported in adult patients. This study aimed to address the lack of data on children with migraine. Methods: This study comprised 30 children and adolescents (16 male) with migraine. We evaluated their biochemical profile, glucose homeostasis, vascular function by flow‐mediated dilatation and arterial structure by carotid intima‐media thickness (cIMT). A group of 32 age, sex and auxologically matched children (17 male) served as controls. Results: The group of children with migraine had a normal biochemical profile and glucose homeostasis, but presented with significantly thicker cIMT than the control group (0.48 ± 0.07 mm versus 0.45 ± 0.04, p < 0.05). Conclusion: We observed a significantly thicker cIMT in children with migraine compared with the controls. The brief time interval between the onset of the disease and the time of the study makes it unlikely that repetitive migraine attacks could be responsible for the thickening of the cIMT. Thus, it may be speculated that primitive vascular function abnormalities were wholly or partly responsible for the development of migraine in this paediatric cohort.